Peningkatan Keterampilan Membaca Teks Pidato Menggunakan Metode Project Based Learning (PJBL) Pada Siswa Kelas V UPT SPF SDN 101922 Beringin - Chindi Gracefva Purba; Indah Rosa Damanik; Putri Azhari; Sunarti Sunarti; Mustika Wati Siregar (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Reading is a way to get information from something written. Reading involves recognizing the symbols that make up a language. Reading and listening are the 2 most common ways to get information. This research is a classroom action research, which is cyclical there are 4 main activities in each cycle, namely: a. Planning b. Implementation / Implementation c. Observation and Evaluation d. Results of analysis and reflection. The data analysis technique used is Content Analysis